An Investigation into The Grammatical Errors of Students’ Writing - Didin Nuruddin Hidayat; Nur Fitriyani; Alek Alek; Yudi Septiawan; Ismalianing Eviyuliawati (Universitas Sulawesi Barat, 2020)
Writing serves as a tool for students to extend their grammatical composition, enrich their lexicon, and increase other language abilities, such as reading, listening, and speaking. This study intends to examine written features and analyze frequent errors of students' grammar in writing. Employing a qualitative descriptive research method, the samples were chosen based on convenience samples. The participants were high schoolers studying at their Year 10, whose English language competence is at an average grade. The students practiced descriptive writing and grammar rules. Four students submitted their essays analyzed using content analysis. The assessment criteria were analyzed using a framework of grammatical errors by James (1998), which classify errors into nine (9) categories (prepositions, articles, singular/plural, adjectives, irregular verbs, tenses, concord, possessive case, and passive/active). The study found 73 errors in students’ writing. The top three errors found were prepositions, articles, and tenses, in a particular order. The next identified errors were singular/plural, concord, possessive case, and irregular verbs. Some pedagogical implications deriving from the study were also highlighted. The present study suggests the need for EFL teachers to improve their skills in marking and giving feedback toward student writing. This will, in turn, improve students’ writing skills.